2021
DOI: 10.1002/adma.202005890
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Color: The New Carbon Ink

Abstract: For thousands of years, carbon ink has been used as a black color pigment for writing and painting purposes. However, recent discoveries of nanocarbon materials, including fullerenes, carbon nanotubes, graphene, and their various derivative forms, together with the advances in large‐scale synthesis, are enabling a whole new generation of carbon inks that can serve as an intrinsically programmable materials platform for developing advanced functionalities far beyond color. The marriage between these multifuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 238 publications
(357 reference statements)
0
26
0
Order By: Relevance
“…This strategy works even for nanotubes of small diameters (∼0.78 nm), which are susceptible to thermal oxidation at elevated temperatures. This work provides new insights for the choice or design of surfactants in applications such as electrical sensors, , printable electronics, , and optoelectronics where the clean removal of the surfactant after solution processing is key to enhanced device performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy works even for nanotubes of small diameters (∼0.78 nm), which are susceptible to thermal oxidation at elevated temperatures. This work provides new insights for the choice or design of surfactants in applications such as electrical sensors, , printable electronics, , and optoelectronics where the clean removal of the surfactant after solution processing is key to enhanced device performance.…”
Section: Discussionmentioning
confidence: 99%
“…Single-walled carbon nanotubes (SWCNTs) are a family of cylindrical carbon allotropes that exhibit extraordinary electrical, optical, and mechanical properties. 1−3 Because these carbon nanomaterials are synthesized as a heterogeneous mixture of different structures that bundle strongly, polymers 4−8 and surfactants, 9−11 such as sodium dodecyl sulfate (SDS) and sodium deoxycholate (DOC), are widely used to disperse SWCNTs in solution for subsequent purification, 12 fiber spinning, 13 ink formulation, 14 and the fabrication of highperformance nanoelectronic devices. 10 However, after solution processing, surfactants become unwanted contaminants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to many advantages such as good electrical conductivity, high chemical and thermal stability, and light weight, many carbon materials, including graphene, graphene oxide (GO), and carbon nanotubes (CNTs), are widely used as humidity-sensitive materials. Xiaoyu Li et al reported a novel high-performance humidity sensor based on graphene oxide/multiwalled carbon nanotubes, and the synergistic effect of this GO/MWCNTs composite resulted in greatly improved performance of the sensor in all aspects . However, humidity sensors based on carbon materials still face a few problems in practical applications, such as the ease in agglomeration of graphene and carbon nanotubes, high cost, toxicity, and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers are good candidates for use as functional dispersants [ 13 ] because extended π-structures bearing solubilizing units (e.g., alkyl chains) can bind noncovalently through π-π interactions to SWCNTs, allowing the formation of SWCNT suspensions. Subsequently, such suspensions can be used to make solution-processed SWCNT films using coating and printing techniques [ 14 ]. However, the solubilizing conjugated polymer remains attached to the surface of the SWCNTs, meaning that the resulting film can be damaged upon exposure to the solvent in which it was made.…”
Section: Introductionmentioning
confidence: 99%